A study on electric field mapping from the F region to the E region at Arecibo. Issue 1 (20th January 2016) - Gong, Yun; Zhou, Qihou; Zhang, Shaodong
Abstract: We present the first direct comparison of the vertical electric fields in the E and F regions at Arecibo. The electric field is generally assumed to be height invariant and can be mapped from the F region to the E region along the magnetic field line. We develop a method to verify the electric field mapping by comparing the E and F region eastward ion drifts at heights where the E region vertical ion drift is zero. Our method avoids using the ion‐neutral collision frequency, which is considered to be the most uncertain parameter in computing the E region electric field using radar measurements. The results show that the F region eastward E × B ion drift and the E region eastward ion drift at locations where vertical ion drift equals zero are not consistent. This implies that the E region vertical electric field is not the same as that from the F region. Key Points: Electric fields in the E region and F region are not the same as commonly assumed E region electric field is measured with minimal assumptions Need to reexamine our practice of using ISR to measure neutral winds